2012
DOI: 10.1007/s12149-012-0616-1
|View full text |Cite
|
Sign up to set email alerts
|

Salivagram revisited: justifying its routine use for the evaluation of persistent/recurrent lower respiratory tract infections in developmentally normal children

Abstract: Antegrade pulmonary aspiration can be demonstrated as an underlying cause for persistent/recurrent lower respiratory tract infection in developmentally normal children, with age being an important clinical predictor. Combined use of salivagram and milk scan is warranted to objectively evaluate pulmonary aspiration in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Therefore, this approach is useful to improve the detection accuracy of salivary aspiration. All salivary aspiration was observed in the initial dynamic acquisition phase of the study, which is consistent with the previously reported data (12). However, the occurrence time of aspiration varied among the included patients; thus, further studies are needed to determine whether aspiration time point is associated with the severity of AECOPD.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, this approach is useful to improve the detection accuracy of salivary aspiration. All salivary aspiration was observed in the initial dynamic acquisition phase of the study, which is consistent with the previously reported data (12). However, the occurrence time of aspiration varied among the included patients; thus, further studies are needed to determine whether aspiration time point is associated with the severity of AECOPD.…”
Section: Discussionsupporting
confidence: 88%
“…However, it is mostly used in pediatric patients (9)(10)(11)(12), and no previous study has assessed its utility in AECOPD patients. Furthermore, in all studies of radionuclide salivagram, only traditional planar images were obtained, and the poor spatial and temporal resolution of planar images and the lack of anatomic landmarks are limiting factors.…”
Section: Introductionmentioning
confidence: 99%
“…Drubach et al found a similar frequency of positive salivagrams (25%) in 222 children, with high agreement (kappa = 0.891, P  < 0.0001) between salivagram and chest X-ray findings (48). In a study of developmentally normal children with recurrent lower respiratory tract infections, Somasundaram et al found positive salivagrams in 39% of infants and 16% of children aged 1–2 years (49). There was no aspiration noted in children over the age of 2 years.…”
Section: Diagnosing Aspiration During Swallowingmentioning
confidence: 99%
“…Even if heart disease symptoms manifest in a kid beyond the age of three, this may be regarded as a premature onset. Reducing the threshold of the bronchial reactivity that is organically connected to the congenital malformation image, heart illness (39,40) and atopy possibly expedites the development of symptoms. This adds to respiratory morbidity.…”
Section: Discussionmentioning
confidence: 99%